Progressive reduction in treatment-related deaths in Medical Research Council childhood lymphoblastic leukaemia trials from 1980 to 1997 (UKALL VIII, X and XI). - Hargrave, DR; Hann, I; Richards, S; Hill, F; Lilleyman, J; Kinsey, S; Bailey, C; Chessells, J; Mitchell, C; Eden, O (2001)
In the last 20 years, the survival rate for children with acute lymphoblastic leukaemia (ALL) has markedly improved, largely owing to a decrease in relapses. However, children still die from complications of treatment and these are potentially preventable. We have analysed data from three large consecutive national protocols for ALL from 1980 to 1997 [Medical Research Council United Kingdom ALL (MRC UKALL) trials VIII, X and XI] to compare the incidence and causes of treatment-related deaths (TRD). The percentage of TRD has fallen from 9% to 2% (UKALL VIII to XI), largely as a result of a decrease in fatal infections. Deaths during induction have fallen from 3% to 1%, the main causes of death being bacterial, followed by fungal infection, while other causes, chiefly haemorrhage, have not declined. Remission deaths also decreased from 6% to 1%, particularly those deaths due to measles and pneumocystis carinii. More guidelines for surveillance and treatment of infections have been included within progressively more intensive protocols. Risk factor analysis showed increased TRD in patients with Down's syndrome, high leucocyte count and older age in UKALL XI. In contrast, the introduction of blocks of intensification was not associated with an increased death rate. While improved supportive care has reduced the incidence of TRD, there is still scope for further reduction by prompt treatment of suspected infection. Maintenance of herd immunity remains of vital importance in avoiding deaths from measles.